2007
DOI: 10.1080/13546800600750597
|View full text |Cite
|
Sign up to set email alerts
|

Hopping, skipping or jumping to conclusions? Clarifying the role of the JTC bias in delusions

Abstract: A tendency to gather less evidence in the Beads task is reliably associated with the presence of delusional symptomatology. In contrast, certainty on the task, and responses to contradictory evidence, do not discriminate well between those with and without delusions. The implications for the underlying basis of the JTC bias, and its role in the formation and maintenance of delusions, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
213
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(238 citation statements)
references
References 48 publications
11
213
2
12
Order By: Relevance
“…Indeed, the regression analysis showed that depression was the variable that best predicts delusional ideation and explains the most variance. However, in both cases, these findings are in accordance with the relative null effect that emotional valence has on JTC (for a review, see Fine et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Indeed, the regression analysis showed that depression was the variable that best predicts delusional ideation and explains the most variance. However, in both cases, these findings are in accordance with the relative null effect that emotional valence has on JTC (for a review, see Fine et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…However, they did not display a hasty decision making in their change of mind, suggesting that delusions may not be associated with a tendency to jump to new conclusions, but rather with a tendency to change conclusions. The concept of jumping to new conclusions has been considered with reservation (Fine et al, 2007) as it is often regarded as being at odds with an element of the usual definition of delusions: that they are "fixed false beliefs" (Sadock and Sadock, 2003). However, if people with delusions and people with delusional ideation jump to one conclusion, it had to be tested whether they jump again to another conclusion as quickly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…characteristic of patients prone to severe pathology. This link between changes in cognition and changes in symptom severity has been demonstrated with the jumping-to-conclusions (JTC) bias (Woodward et al 2009;Sanford et al 2013), a distinct but related cognitive process thought to be associated with delusions (Garety et al 1991;Fine et al 2007;Freeman et al 2008;Speechley et al 2010;Menon et al 2013).…”
Section: Limitationsmentioning
confidence: 96%